Glomus Tumor of Finger Pulp - A Case Report - Rahman, Md Moklesur; Akhter, Nasima; Iqbal, Abu Khaled Muhammad; Waheed, SM Shameem; Rahman, AKM Sharifur; Alam, Md Nur (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Glomus tumors are rare, vascular,benign, painfulneoplasm, originating from glomus bodies and comprise just 1% of tumors arising in the hand, with fewer than 10% in the volar pulp of digits. Hallmark symptoms of glomus tumors include hypersensitivity to cold, heightened pinprick sensitivity and paroxysmal pain. We report this case due to its rarity and it’s potentialto be included among the differential diagnosis if the lesion is painful. We report here a rare case of a 59-years male presenting with08-years history of pain in the palmer surface of distal phalanx of right little finger. The fingertip was incredibly sensitive to touchand the pain increased at night. He could not recollect any history of trauma. Palpation of the finger revealed tenderness with feeling of no lump. Magnetic resonance imaging(MRI) of the right little finger revealed a small altered signal intensity lesion measuring about 8.0x4.0mm at the ventral aspect of distal phalanx ofright little finger. After I/V contrast- moderate enhancement of the lesion is seen. An incision was made in the mid-axial plane. A circumscribed mass removed with careful &blunt dissection. It was a tan-yellow, soft tissue nodule of about 1- cm in diameter without stalk or adherences to joint capsule or bone. Histopathological examination revealed the mass as a glomus tumor. Symptoms improved on removal and the wound healed without complications. Glomus tumors in the volar digital pulp can be difficult to diagnose. Complete surgical excision of the tumor is the only effective treatment to achieve pain relief and low recurrence.We also emphasize the importance of keeping this tumor in mind among the possibilities of differential diagnosis of painful digital nodules. J Bangladesh Coll Phys Surg 2022; 40: 306-309